How the Lack of Chitosan Characterization Precludes Implementation of the Safe-by-Design Concept - Marques, Cíntia; Som, Claudia; Schmutz, Mélanie; Borges, Olga; Borchard, Gerrit (Frontiers in Bioengineering and Biotechnology, 2020)
Efficacy and safety of nanomedicines based on polymeric (bio)materials will benefit from a rational implementation of a Safe-by-Design (SbD) approach throughout their development. In order to achieve this goal, however, a standardization of preparation and characterization methods and their accurate reporting is needed. Focusing on the example of chitosan, a biopolymer derived from chitin and frequently used in drug and vaccine delivery vector preparation, this review discusses the challenges still to be met and overcome prior to a successful implementation of the SbD approach to the preparation of chitosan-based protein drug delivery systems.